2018
DOI: 10.1128/mcb.00304-18
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal RACK1:Protein Kinase C βII Phosphorylates Eukaryotic Initiation Factor 4G1 at S1093 To Modulate Cap-Dependent and -Independent Translation Initiation

Abstract: Eukaryotic ribosomes contain the high-affinity protein kinase C βII (PKCβII) scaffold, receptor for activated C kinase (RACK1), but its role in protein synthesis control remains unclear. We found that RACK1:PKCβII phosphorylates eukaryotic initiation factor 4G1 (eIF4G1) at S1093 and eIF3a at S1364. We showed that reversible eIF4G(S1093) phosphorylation is involved in a global protein synthesis surge upon PKC-Raf-extracellular signal-regulated kinase 1/2 (ERK1/2) activation and in induction of phorbol ester-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
0
18
1
Order By: Relevance
“…We thus employed RACK1 knockout cells generated by CRISPR-Cas9 mediated genome editing (45) and transduced them with lentiviruses to express RACK1-FLAG, which was incorporated into translating ribosomes (figure 1). In contrast to others who have reported that RACK1 depletion reduces cap-dependent translation (30, 56), we do not observe major changes in cap-dependent translation in RACK1 KO cells ((45), figure 4A and unpublished data). It is possible that the contrasting observations are due to cell line specific differences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We thus employed RACK1 knockout cells generated by CRISPR-Cas9 mediated genome editing (45) and transduced them with lentiviruses to express RACK1-FLAG, which was incorporated into translating ribosomes (figure 1). In contrast to others who have reported that RACK1 depletion reduces cap-dependent translation (30, 56), we do not observe major changes in cap-dependent translation in RACK1 KO cells ((45), figure 4A and unpublished data). It is possible that the contrasting observations are due to cell line specific differences.…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that the contrasting observations are due to cell line specific differences. While HAP1 cells are derived from the chronic myelogenous leukemia (CML) cell line KBM-7, all studies that found that RACK1 influenced cap-dependent and -independent translation were performed in HEK293, HEK293T, and HeLa cells (30, 31, 56). Since RACK1 stimulates global translation in a PKCβII-dependent manner (30, 43), potentially higher PKCβII expression levels found in HEK293 and HeLa cells or other cell line-specific differences might explain the opposing effect on translation ((57), https://www.proteinatlas.org/ENSG00000166501-PRKCB/cell).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lines, DNA transfections, and eIF4G expression plasmids. HEK293 cells were grown, transfected, synchronized, and treated with kinase inhibitors and/or activators as described earlier (4). Construction of Myc/Flag-tagged eIF4G expression plasmids has been described previously (4); the eIF4G fragments used in this study were generated by PCR with the corresponding primers (Table 1), and mutations were introduced by overlapping PCR as described earlier (4).…”
Section: Methodsmentioning
confidence: 99%
“…phorbol-13-acetate (TPA)-responsive template-specific translation in an eIF4G-, PKC␤-, and RACK1-dependent manner (4). We showed anomalous TPA-inducible eIF3 binding to nonphospho (S1093A) or phosphomimic (S1093E) variants of eIF4G, indicating that reversible S1093 phosphorylation regulates eIF4G's assembly with eIF3 and 40S ribosomal subunits (4).…”
mentioning
confidence: 97%